Azathioprine as an adjuvant therapy in severe Graves’ disease: a randomized controlled open-label clinical trial - Allam, Magdy Mohamed; El-Zawawy, Hanaa Tarek; Kader Okda, Amr Abdel; Ali Alshaikh, Ayoub; Ghazy, Ramy Mohamed (Frontiers in Endocrinology, 2023)
Introduction Azathioprine (AZA) interferes with the activation of T and B lymphocytes, which are the main cells involved in the pathogenesis of Graves’ disease (GD). The aim of this study was to investigate the effectiveness of AZA as an adjuvant therapy to antithyroid drugs (ATDs) for moderate and severe GD. In addition, we conducted an incremental cost-effectiveness analysis of AZA to determine its cost-effectiveness. Methods We conducted a randomized, open-label, and parallel-group clinical trial. We randomized untreated hyperthyroid patients with severe GD into three groups. All patients received 45-mg carbimazole (CM) as the starting dose and propranolol 40–120 mg daily. The first group (AZA1) received an additional 1 mg/kg/day AZA, the second group (AZA2) received an additional 2 mg/kg/day AZA, and the third group (control group) received only CM and propranolol. We measured thyroid-stimulating hormone (TSH) and TSH-receptor antibody (TRAb) levels at baseline and every 3 months, while free triiodothyronine (FT3) and free thyroxine (FT4) levels were measured at the time of diagnosis, 1 month after initiation of therapy, and every 3 months thereafter until 2 years after remission. Thyroid volume (TV) was assessed by ultrasound at baseline and 1 year after remission. Results A total of 270 patients were included in this trial. By the end of follow-up, there was higher remission rate in the AZA1 and AZA2 groups compared with controls (87.5% and 87.5% vs. 33.4%, p = 0.002). Throughout the course of follow-up, FT3, FT4, TSH, and TRAb were significantly different between the AZA groups and the control group, but there was no significant difference regarding TV. The decline in the concentrations of FT4, FT3, and TRAb was significantly faster in the AZA2 group than in the AZA1 group. The relapse rate during the 12-month follow-up was insignificantly higher in the control group than in either the AZA1 or AZA2 group (10, 4.4, and 4.4%, p = 0.05, respectively). The median relapse time was 18 months for the control group and 24 months for the AZA1 and AZA2 groups. The incremental cost-effectiveness ratio for the AZA group compared with the conventional group was 27,220.4 Egyptian pounds per remission reduction for patients using AZA as an adjuvant for ATDs. Conclusion AZA could be a novel, affordable, cost-effective, and safe drug offering hope for patients with GD to achieve early and long-lasting medical remission. Trial registry The trial is registered at the Pan African Clinical Trial Registry (Registration number: PACTR201912487382180).